Synthesis, Spectral and Bacterial Studies of Mixed Ligand Complexes of Schiff Base Derived from Methyldopa and Anthranilic Acid with Some Metal Ions - Al-Obidi, L.K; Al-Noor, T.H . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Bidentate Schiff base ligand 3-(3,4-Dihydroxy-phenyl)-2-[(4-dimethylamino-benzylidene)-amino]-2-methyl-propionic acid was prepared and characterized by spectroscopic techniques studies and elemental analysis. The Cd(II), Ni(II), Cu(II), Co(II), Cr(III),and Fe(III) of mixed-ligand complexes were structural explicate through moler conductance , [FT-IR, UV-Vis & AAS], chloride contents, , and magnetic susceptibility measurements. Octahedral geometries have been suggested for all complexes. The Schiff base and its  complexes were  tested against various bacterial species, two of {gram(G+) and gram(G-)} were shown weak to good activity against all bacteria.